Precision functional mapping of the subcortex and cerebellum. (August 2021) - Marek, Scott; Greene, Deanna J
Highlights: Precision functional mapping enables reliable maps of individual brain networks. This method has been extended to characterize subcortical and cerebellar organization. Subcortex contains integration zones with variable consistency across individuals. Cerebellum contains overrepresentation of the frontoparietal network in all subjects. Precision functional mapping of these structures holds promise for clinical utility. Abstract : Human functional brain networks can be reliably characterized within individuals using precision functional mapping. This approach entails the collection of large quantities of functional magnetic resonance imaging (fMRI) data from each individual subject. Studies employing precision functional mapping in the cerebral cortex have found that individuals manifest unique representations of functional brain networks around a central tendency described by previous group average approaches. We recently extended precision functional mapping to the subcortex and cerebellum, which has revealed several novel organizational principles within these structures. Here, we detail these principles and provide insights into how precision functional mapping of subcortical structures and the cerebellum may become clinically translatable.